High parathormone levels are associated with adverse cardiovascular events in coronary patients with high fibroblast growth factor-23. (25th November 2020) - Gutierrez, C; Acena, A; Pello, A; Martinez-Milla, J; Gonzalez-Lorenzo, O; Tarin, N; Cristobal, C; Huelmos, A; Lopez-Castillo, M; Alonso, J; Gonzalez-Parra, E; Egido, J; et al.
Abstract: Background: Disturbances of the components of the mineral metabolism (MM) (vitamin D, phosphate, parathormone [PTH], fibroblast growth factor-23 [FGF23] and klotho) have been linked to cardiovascular disease. However, the available data are controversial, probably because most studies deal with individual rather than with the whole MM components. Purpose: To the study the relationship between MM components and cardiovascular events, after controlling for other well-known markers (N-Terminal pro-brain natriuretic peptide [NT-proBNP], high-sensitivity troponin I [hs-TnI], and high-sensitivity c-reactive protein [hs-CRP]), and relevant clinical variables in stable coronary artery disease (CAD) patients. Methods: We analyzed the aforementioned markers in 964 CAD patients and followed them subsequently. The primary outcome (PO) was the composite of ischemic events (acute coronary syndrome, stroke or transient ischemic attack), heart failure and death. Secondary outcomes were any ischemic event and the composite of heart failure and death. Results: Median follow-up was 5.39 years (2.81 - 6.92). Age was 60 (52–72) years and 76.2% patients were male. Median glomerular filtration rate was 80.4 (65.3–93.1) ml/min/1.73 m 2 . 185 patients developed the PO. At the univariate analysis PTH, FGF23, NT-proBNP and hs-TnI were directly associated with the PO, while calcidiol and Klotho were inversely related, and phosphate did not reach statistical significance. However, only PTH (HR 1.058 [CI 1.021–1.097]; p=0.002) and NT-proBNP (HR 1.020 [CI 1.012–1.028]; p<0.001) were independent predictors of the PO at multivariate Cox regression analysis. Both PTH and NT-proBNP were also independent predictors of HF or death (HR 1.066 [1.016 - 1.119]; p=0.009 and HR 1.024 [1.014 - 1.034]; p<0.001 respectively), while only PTH predicted ischemic events (HR 1.052 [1.010–1.096]; p=0.016). After dividing patients in two subgroups according to whether they had FGF23 plasma levels above the median (85.5 RU/ml) or not, PTH remained as a predictor of the PO only in the subgroup with FGF23 >85.5 RU/ml (p<0.001), but not in patients with FGF23 ≤85.5 RU/ml (p=0.551). There was a significant interaction between FGF23 and PTH plasma levels (p=0.002). Conclusion: PTH predicts cardiovascular events in CAD patients with elevated FGF23 levels even after taking into account all the other components of MM and controlling for NT-ProBNP, hs-CPR and TnI. There is an interaction between PTH and FGF23 levels, and they should be assessed together when exploring their potential predictive power. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Fondo de Investigaciones Sanitarias